Akuntabilitas dan Transparansi Keuangan sebagai Imperatif Moral: Tinjauan Etika Deontologis Kant terhadap Kinerja Pegawai KSP Kopdit Obor Mas Maumere - Yohanes Gualberthus Embu Geju; Eugenius Besli (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study analyzes the influence of accountability and financial transparency on employee performance at KSP Kopdit Obor Mas Maumere using Immanuel Kant’s deontological ethics as a theoretical framework. A mixed methods approach was employed, combining quantitative surveys and in-depth interviews. Quantitative data were analyzed using multiple linear regression, while qualitative data were examined through thematic analysis to enrich the statistical interpretation. The findings reveal that accountability (sig. 0.001 < 0.05) and financial transparency (sig. 0.000 < 0.05) have positive and significant effects on employee performance, both partially and simultaneously, explaining 77.1% of performance variation. Financial transparency demonstrates a more dominant influence than accountability. Qualitative results confirm that audit practices, Annual Member Meetings (RAT), financial disclosure, and accurate data provision have been institutionalized as moral obligations rather than merely administrative mechanisms. From a Kantian categorical imperative perspective, accountability and transparency are practiced as universal duties grounded in honesty, responsibility, and respect for members as moral subjects. This study highlights that cooperative governance rooted in moral obligation not only strengthens organizational integrity but also substantially enhances employee performance.